2021 IEEE/ACM 43rd International Conference on Software Engineering (ICSE) 2021
DOI: 10.1109/icse43902.2021.00077
|View full text |Cite
|
Sign up to set email alerts
|

Can Program Synthesis be Used to Learn Merge Conflict Resolutions? An Empirical Analysis

Abstract: Forking structure is widespread in the open-source repositories and that causes a significant number of merge conflicts. In this paper, we study the problem of textual merge conflicts from the perspective of Microsoft Edge, a large, highly collaborative fork of the main Chromium branch with significant merge conflicts. Broadly, this study is divided into two sections. First, we empirically evaluate textual merge conflicts in Microsoft Edge and classify them based on the type of files, location of conflicts in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 26 publications
(33 reference statements)
4
21
0
Order By: Relevance
“…Some other studies characterize the root causes and/or resolutions of textual conlicts [18,29,37,50,53,58]. Speciically, Ji et al studied the textual conlicts caused by Git RebaseÐa practice to merge program changes by rewriting the evolution history [37].…”
Section: Empirical Studies On Merge Conflictsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some other studies characterize the root causes and/or resolutions of textual conlicts [18,29,37,50,53,58]. Speciically, Ji et al studied the textual conlicts caused by Git RebaseÐa practice to merge program changes by rewriting the evolution history [37].…”
Section: Empirical Studies On Merge Conflictsmentioning
confidence: 99%
“…They observed that 44% of conlicts were caused by conlicting updates to the same line of code, and developers resolved 99% of conlicts by taking either the left-or right-version of code. Pan et al studied 271 merging scenarios with textual conlicts inside the repository of Microsoft Edge [53]. The researchers clustered scenarios based on the ile types, conlict sizes, conlict locations, and resolution patterns.…”
Section: Empirical Studies On Merge Conflictsmentioning
confidence: 99%
“…They do not automate the task of synthesizing a rule from a cluster of code changes. Program synthesis has also been recently applied to other code related applications such as API migration [Gao et al 2021;Ni et al 2021], synthesis of merge conflict resolutions [Pan et al 2021], interactive code search ]. Datalog synthesis: There is a rich body of recent work on datalog synthesis [Albarghouthi et al 2017;Si et al 2018Si et al , 2019Thakkar et al 2021] and its application to code related tasks such as interactive code search .…”
Section: Related Workmentioning
confidence: 99%
“…Gulwani [20] introduced FlashFill to synthesize string transformation scripts from examples. In the software engineering domain, there have been efforts to apply program synthesis techniques on code related tasks such as learning version update patches [5], code edit scripts [43], and merge conflict resolutions [52]. However, our work targets a new domain that has not been explored using PBE: software documentation.…”
Section: Related Workmentioning
confidence: 99%